Territorial and duet calls of three Malaysian owl species - Yee, Siew Ann; Puan, Chong Leong; Chang, Phooi Kuan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Vocalisations of tropical birds are still largely unexplored particularly the nocturnal species. This study examined and quantitatively described the territorial calls and duets of the Sunda Scops-Owl (Otus lempiji), Brown Boobook (Ninox scutulata) and Spotted Wood-Owl (Strix seloputo) based on 105 territorial call and four duetting recordings collected from one forest reserve and oil palm smallholdings in Selangor, Peninsular Malaysia. Wilcoxon signed-rank tests found significant differences (p<0.05) for almost all vocal parameters measured from the spectrograms derived from the duets with one higher-pitched than the other. Being the first study to describe the vocal structure of the duetting calls of the three Malaysian strigids, this study serves as a baseline for future behavioural study of nocturnal birds particularly pertaining to conspecific interactions in the Sunda region.